(untitled) (Annals of Bangladesh Agriculture, 2025)
The approach of chemical mutagenesis has proven effective in enhancing crop genetic variation. Out of the many different chemical mutagens available, ethyl methanesulfonate (EMS) is commonly used in crops because of its high frequency of causing DNA changes, which can be observed in several genomes. Various concentrations, ranging from 1.2% to 2% of EMS were administered to cherry tomatoes to compare their effects with a Control group. The objective was to determine these concentrations’ effectiveness in improving the cherry tomatoes’ morphological and biochemical characteristics. Significant variations were noticed in the morphological and biochemical characteristics compared to the Control. 1.4% EMS was linked to characteristics associated with earliness, but 1.2% EMS positively impacted the quantity of fruits produced per plant. The use of 2% EMS treatment resulted in a higher number of branches per plant, but it did not have any discernible positive effect on production. The correlation studies indicated a moderate positive link between the height of plants and the quantity of fruits produced per plant. The EMS treatment resulted in significant alterations, as observed through biochemical tests. A concentration of 1.2% EMS showed positive effects on lycopene and ascorbic acid, but a concentration of 1.4% EMS resulted in improved levels of chlorophyll a, chlorophyll b, and carotenoids. Chlorophyll b showed good performance with a concentration of 1.6% EMS; however, a concentration of 2% EMS was more effective in increasing phenolic and antioxidant content. The experiment’s results revealed that EMS-induced mutagenesis is a valuable tool for enhancing agronomic and yield-related traits and biochemical features. In addition, mutants possessing yield-related beneficial characteristics will be accessible to researchers for high-level investigation. They will also function as a genetic resource for advancing and improving breeding strategies. Ann. Bangladesh Agric. 28(1): 145-156